Chemically fabricated ZnO/Ag/AgmMonOl/ZnxMoyOz heterojunction nanophotocatalysts for abating organic dyes in wastewater. (20th August 2022) - Bai, Liming; Guo, Ruibo; Chen, Zhao; Liu, Lumin; Dong, Guohua; Zhang, Jianwei; Wu, Yang; Zhao, Huaping; Shan, Dan; Su, Yuanyuan; Zhang, Jiyuan; Wang, Baiqi
Abstract: Semiconductor photocatalytic technology is among the most promising technologies for degrading organic pollutants in wastewater. However, broadening the photocatalytic spectral-response region of the nanomaterial and tuning carrier behavior at heterojunction interfaces remain wastewater-treatment challenges. To address this issue, we fabricated ZnO/Ag/Ag m Mo n O l /Zn x Mo y O z (ZAAZ) heterojunction nanophotocatalysts through a simple one-step chemical reaction between active ZnO nanoparticles and Ag/Ag x H3− x PMo12 O40 (Ag/AgPMo). The as-prepared ZAAZ heterojunction nanophotocatalysts were physically and chemically characterized, photocatalytic activity was evaluated, and the photogenerated carrier-transfer mechanism analyzed. The optimal nanophotocatalyst was highly crystalline and exhibited a bandgap and specific surface area of 3.06 eV and 13.9 m 2  g −1, respectively; it photodegraded almost 100% of the initial Rhodamine B (RhB) concentration in 90 min under the optimized conditions, which is 3.7-times faster than ZnO nanoparticles. Furthermore, the ZAAZ heterojunction nanophotocatalyst delivered a photocurrent of 8.3 μA cm −2, which is 31-times higher than that of its ZnO nanoparticle counterpart; it efficiently separated photogenerated carriers, transferred interfacial charges, and degraded 97% of the initial RhB concentration after three cycles of use, highlighting its excellent recyclability. These findings suggest that the developed heterojunction nanophotocatalyst is highly efficient for the photocatalytic degradation of organic water pollutants. Graphical abstract: Image 1